STUDI OBSERVASI TERHADAP RENDAHNYA KUNJUNGAN PASIEN RAWAT JALAN PELAYANAN MEDIK SPESIALISTIK LAIN - WENNY RETNO SARIE LESTARI; FIDA RAHMAYANTI; VIVA MAIGA MAHLIAFA NOOR (AKADEMIKA, 2018)
Promotion and decision making from customer have positive relation. Marketing promotion mix is one of a promotion communication tools in a company. Preeliminary study in Muhammadiyah Malang University Hospital (UMM Hospital) showed that patient visitation from other medical specialistic is still low. This study objectives are to know the factors of low patient visitation to other medical specialistic in UMM Hospital. Methodology used in this study are observation, focus group discussion (FGD), documents review, and interview. The study result shows that there are no monitoring and evaluation that has been done to promotion activities, therefore promotion activities are not maximal. Solution that agreed to UMM Hospital are making guideline and standard operational of procedurs (SOP) of monitoring and evaluation of promotion activities, and quistionnare to patient visitation in UMM Hospital.